When Does an Interest Rate Path "Look Good"? Criteria for an Appropriate Future Interest Rate Path - Jan F. Qvigstad (Norges Bank, 2006)
Svensson (2004) suggested that a monetary policy committee of a central bank (MPC) should "find an instrument-rate path such that projections of inflation and output gap 'look good'." Academic literature on monetary policy gives guidance as to what the words "look good" means. However, there is a need for a translation of the theoretical framework into concrete criteria when an MPC shall evaluate interest rate paths in practice. Six criteria for an appropriate interest rate path are presented. In the November 2005 Inflation Report, Norges Bank presented for the first time an optimal interest rate path including a fan chart illustrating the uncertainty of the forecast using these criteria. Examples used in explaining the criteria are drawn from Norwegian experiences.
hdl:11250/2498372
Keywords: E42; E52; E58; 330; forecasts; flexible inflation targeting; optimal monetary policy